2022
DOI: 10.1002/ppul.25966
|View full text |Cite
|
Sign up to set email alerts
|

HIDEA syndrome: A rare cause of congenital hypoventilation in a premature infant

Abstract: Background: HIDEA (hypotonia, hypoventilation, intellectual disability, dysautonomia, epilepsy and eye abnormalities) syndrome is a rare and novel disease. We describe a premature patient who required extensive work up for his hypoventilation with a diagnosis of HIDEA syndrome.Case Description: The patient was born to a pair of consanguineous parents at 32-week gestation. His intermittent bradypnoea requiring significant respiratory support during his postnatal clinical course was atypical for bronchopulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Here, we report six new unrelated patients and review the clinical details of all 24 previously published HIDEA patients. The phenotype of the patients identified in the current study is comparable to the phenotype described in the literature 1,2,5–8 . One patient in this study has dystonia, which has not previously been described in HIDEA.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Here, we report six new unrelated patients and review the clinical details of all 24 previously published HIDEA patients. The phenotype of the patients identified in the current study is comparable to the phenotype described in the literature 1,2,5–8 . One patient in this study has dystonia, which has not previously been described in HIDEA.…”
Section: Discussionsupporting
confidence: 85%
“…To the authors' knowledge, P4HTM p.(Glu312Lys), p.(Thr361Ile), and p.(Trp457*) variants have not previously been reported as disease‐causing, hence expanding the genotypic spectrum of the disease. To date, including the cases reported in the present study, there are 15 different pathogenic variants of P4HTM reported to cause HIDEA syndrome 1,2,5–8 …”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations